Microcontroller-Based Automatic Treatment Skin Treater Design - Rama Okta Wiyagi; Anna Nur Nazilah Chamim; Muhamad Yusvin Mustar; Adi Nugroho; Yessi Jusman (Journal of Electrical Technology UMY, 2018)
Rubber or rubber trees (Hevea brasiliensis) is one of the export commodities that become the source of income for the state income. From year to year, the increasing demand for rubber in various areas is very significant. Dusun IV Bandar Sidomulyo is a hamlet located in Lempuyang Bandar Village, Way Pengubuan Subdistrict, Central Lampung Regency with ± 200 houses where source of livelihood is still depend on rubber plantation. So the residents must be willing to peel the skin of rubber plants at early days to get maximum rubber yield. The prototype of Automatic Rubber Tree Tool based on Microcontroller that has been designed works peeling the bark of a tree with depth 1,5 mm with Duwet or Jamblang (Syzygium cumini) trees as an object, so that the tool can be used to peel rubber automatically on rubber trees generally.